Batasan Yuridis Penerima Hibah Pelaku Pasif Tindak Pidana Pencucian Uang dengan Harta Kekayaan dari Hasil Tindak Pidana Korupsi - Wisnu Kumara Putra; Riska Andi Fitriono (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to find out the juridical limits, before grant recipients with the donated assets originating from the criminal acts of corruption can be threatened with criminal penalties based on Act Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering as passive perpetrators of money laundering crimes. This research is a normative type of research that is prescriptive in nature, and is based on a statute, case, historical, and the conceptual approach. This research is based on legal materials consisting of primary and secondary legal materials, which were carried out by studying library materials, then analyzed through a deductive mindset using the syllogism method. Based on this research, the results obtained are that grant recipients with donated assets originating from assets that resulting from criminal acts of corruption can be punished as passive perpetrators of money laundering crimes, if the grant recipient has fulfilled the elements of the act as stated in the formulation of Article 5(1) Act Number 8 of 2010 concerning Prevention and Eradication of the Crime of Money Laundering. However, apart from fulfilling the elements of action according to this article, in order to be responsible for their actions, the recipient of the grant must have been proven to have made a mistake, for which there is no forgiving reason that can erase the mistake.